Factors Impacting Echocardiographic Imaging after the Fontan Procedure: A Report from the Pediatric Heart Network Fontan Cross‐Sectional Study. Issue 9 (25th April 2013) - Williams, Richard V.; Margossian, Renee; Lu, Minmin; Atz, Andrew M.; Bradley, Timothy J.; Jay Campbell, Michael; Colan, Steven D.; Gallagher, Dianne; Lai, Wyman W.; Pearson, Gail D.; Prakash, Ashwin; Shirali, Girish; et al.
<x xml:space="preserve">Abstract</x> Echocardiographic image quality in Fontan survivors may be limited by a variety of factors. We sought to describe echocardiographic quality and factors associated with study quality in subjects participating in the Pediatric Heart Network Fontan Cross‐Sectional Study. Echocardiograms were obtained at 7 clinical sites using a standard protocol. Quality grading and analysis were performed by a core laboratory. Univariate and multivariable modeling were performed to assess factors associated with quality and ability to obtain images sufficient for prespecified quantitative analysis. A total of 543 echocardiograms were obtained. The quality of echocardiograms improved over the duration of the study. The great arteries, systemic veins, and pulmonary veins were less likely to be adequately imaged than other cardiac structures. Quantitative analysis of ventricular volume was possible in 76% overall, but only 41% of those with mixed ventricular morphology. Factors independently associated with better quality included younger age, levocardia, acquisition of the echocardiogram at a longer time since the beginning of enrollment, absence of a pulmonary artery stent, and clinical site. Patient and center‐specific factors are associated with echocardiographic quality after the Fontan procedure. Increased familiarity and experience with a standard imaging protocol is likely to result in improved quality.